Randomized control trial comparing primary hip spica versus initial traction and hip spica of fracture at or below the junction of the upper and middle third of femur in children (Health Renaissance, 2017)
Background: The debate regarding optimal management of femoral shaft fractures in the pediatric population is still far from resolved. While some consensus exists in the treatment of this injury in children younger than the age of six, opinion still widely divided in children six to 11 years.Objective: The aim of study was to compare the outcome of primary hip spica versus initial traction and hip spica of fracture of shaft of femur at or below the junction of the upper and middle third in children in terms of deformity and fracture healing.Method: A RCT study was carried out in the departments of Orthopedics, B.P.Koirala Institute of Health Sciences, Dharan, Nepal from March 2004 to January 2006. Forty five patients were included in the study in which 22 patients included in early spica casting (group I) and 23 patients in traction with spica casting (group II). The functional outcomes were assessed with Pearson’ Chi-square test, Independent samples test and union was assessed radiologically.Result: There was no statistically significant difference in time of union; all of them united in 8-10 weeks follow up. No significant overall difference in terms of deformity was noted in the two groups(p value-0.306).There was significant difference in terms of hospital stay in both the groups(p value